Order/disorder in electrodeposited aluminum-titanium alloys - Stafford G.R.; Tsuda T.; Hussey C.L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The composition, morphology, and crystallographic microstructure of Al-Ti alloys electrodeposited from two different chloroaluminate molten salt electrolytes were examined. Alloys containing up to 28 % atomic fraction Ti were electrodeposited at 150 °C from 2:1 AlCl3-NaCl with controlled additions of Ti2+. The apparent limit on alloy composition is proposed to be due to a mechanism by which Al3Ti forms through the reductive decomposition of [Ti(AlCl4)3]-. The composition of Al-Ti alloys electrodeposited from the AlCl3-EtMeImCl melt at 80 °C is limited by the diffusion of Ti2+ to the electrode surface. Alloys containing up to 18.4 % atomic fraction Ti are only obtainable at high Ti2+ concentrations in the melt and low current densities. Alloys electrodeposited from the higher temperature melt have an ordered L12 crystal structure while alloys of similar composition but deposited at lower temperature are disordered fcc. The appearance of antiphase boundaries in the ordered alloys suggests that the deposit may be disordered initially and then orders in the solid state, subsequent to the charge transfer step and adatom incorporation into the lattice. This is very similar to the disorder-trapping observed in rapidly solidified alloys. The measured domain size is consistent with a mechanism of diffusion-controlled doman growth at the examined deposition temperatures and times.